LEVEL OF CUSTOMER SATISFACTION USING THE KANO AND ROOT CAUSE ANALYSIS (FISH BONE) METHOD IN INTERNET SERVICE PROVIDER COMPANIES (SP Product Case Study) - Kartinah, Dwi (International Journal Science and Technology, 2023)
The study in this research uses the Kano method and root cause analysis to measure customer satisfaction and find out which attributes are maintained and which attributes are improved. After obtaining the attribute results, they are then implemented in a fishbone diagram to solve the root of the problem, so that a solution to the problem can be found. is at PT Telekomunikasi XYZ. The results of this research showed that customers of SP products were categorized as attractive at 40%, must be 4%, indifferent 28%, one dimensional 28%, according to calculations, the highest value of better (increase) was attribute 2 "SP products are easy to use" is 0.68. Meanwhile, the highest worse (decrease) value was attribute 3 "SP product completeness", with a value of -0.92.